Training to Read the Qur'an to Reduce Stress Levels in Beginners with Type Two Diabetes Mellitus - Nur Habibah (Psikologia : Jurnal Psikologi, 2013)
This research was to know the effectiveness of reading tartil Al-Qur’an training according to waqaf and washal with deep breathing to decrease stres for diabetics sufferer. The condition of the subjects were being stable so they could accept their desease, and after that they could adapt to the desease. This research was quasi experimental involved six diabetics sufferer. The characteristic of subject was: Moslem, able to read tartil Al-Qur’an, age 35 – 55 years old, average social economic level, suffer diabetes minimal for 2 years, got stres score scale average until high, prepare as voluntary of the research, and no consume medicine. This training were given along three weeks and the materials were: diabetes mellitus, stres, reading Al-Qur’an with deep breathing, and done in five times confluence. Data of stres scale collected were analyzed by visual inspection, that were the stres level of the subjects compared between the measurement before and after the treatment, there were differences the stres level of subject before and after the treatment reading Al-Qur’an, for subject 3 and subject 5. Subject 1 and subject 4 the decreased were just little. Subject 2 and subject 6 experienced decrease stres scale score in medium. The decrease were not change the category the subject in medium level. Subject 3 and subject 5 experienced the extramely decrease. The research result showed that with deep breathing for the beginners diabetics sufferer could decrease the stres level, the stres scale score after the training were lower than stres scale score before ther training when the reading Al-Qur’an done continuously and intensively.